Psychological Evaluations and the Right to Privacy: Canon 220 (Roman replies and CLSA advisory opinions ; 2012, 2012)
In a petition for a dispensation from the obligations of Holy Orders for a priest, a Diocesan Bishop raised a question with the Congregation for the Clergy concerning psychological evaluations and the right the privacy. The Congregations response follows.